Auto-tuned Active Filter Design for Lighting System in Buildings - Natthanon Phannil; Sulee Bunjongjit; Santipont Ananwattanaporn (My University, 2025)
The lighting system is a continuously used energy system found in all buildings. This system is highly complex as it includes various types such as incandescent bulbs, fluorescent tubes, HID lamps, and LEDs. These types of loads consist of many electronic components and are significant sources of Auto-Tuned Active Filter signals. These harmonic signals directly affect protective devices and electronic equipment in the building's electrical system. Therefore, reducing the harmonic signals generated by the lighting system is crucial for buildings. Generally, harmonic reduction can be achieved by installing one of three types of filters: active, passive, and hybrid. This research presents the design of an auto-tuned active filter using the MATLAB Simulink and tests it using four lighting load cases. The designed circuit can effectively reduce harmonic signals while also improving the energy efficiency of the building.
Keywords: Building Energy and Comfort Optimization; Embedded Systems and FPGA Design; Color perception and design